Steel–concrete–steel sandwich system in Arctic offshore structure: Materials, experiments, and design - Yan, Jia-Bao; Liu, Xue-Mei; Liew, J.Y. Richard; Qian, Xudong; Zhang, Min-Hong (Materials & design, 2016)
The gravity based structure (GBS) with external Steel–Concrete–Steel (SCS) sandwich ice-resistant wall has been developed for the Arctic oil and gas drilling. This paper firstly reported the experimental studies on the mechanical properties of steel and concretes under Arctic low temperature. With the test data, design equations were developed to incorporate the influences of the low temperature on these mechanical properties. Two types of Arctic GBS structure with flower-conical SCS sandwich shell type and plate type of ice-resistant wall have been developed for the Arctic offshore structure. Besides the studies on the materials, two SCS sandwich prototype shells and plates were, respectively, prepared and tested under patch loading that simulated the localized ice-contact pressure. The structural behaviors of the SCS sandwich structure under patch loading were reported and discussions were made on the influences of different parameters on the structural behavior of the structure. Analytical models were developed to predict the punching shear resistances of the SCS sandwich structure through modifying the code provisions. The accuracies of the developed analytical models were checked through validations against 27 tests in the literature. Corresponding design procedures on resistances of SCS sandwich structure were recommended based on these discussions and validations. [Display omitted] •Novel gravity based Arctic offshore structure is developed to resist ice loads.•Arctic low temperatures improve the mechanical properties of steel and concretes.•Composite action greatly affects the resistances of SCS sandwich structure.•SCS sandwich structures offer satisfactory performance against ice loads.•New equations predict well on resistances of the Arctic SCS sandwich structures.